Application and exploration of virtual simulation experimental platform in the experimental teaching of clinical testing instruments and techniques - Peng, Yucheng; Huo, Yishan; Madinaimu, Abibula; Lv, Jie; Feng, Yangchun; Yang, Jia; Qiao, Wenbin; Guo, Fan; Cheng, Zhenzhen; Ma, Xiumin (SHS web of conferences, 2023)
Clinical laboratory instrumentation and technology is a multidisciplinary, multi-technology, multi-disciplinary cross-discipline, with strong application, theoretical and experimental teaching methods are single and boring, and it is difficult for students to master and understand the abstract content. The laboratory has cooperated with a company to complete the experimental teaching for undergraduate students, and analyzed the advantages of this teaching method and the problems that need to be solved through the questionnaire and formative evaluation, and analyzed and summarized them, so as to provide relevant experience for this kind of courses to adopt the virtual simulation experimental platform and provide directional guidance for the construction and development of the virtual simulation experimental platform. Clinical laboratory instrumentation and technology is a multidisciplinary, multi-technology, multi-disciplinary course, which is highly applied, rapidly developing, and has a short update cycle, and is one of the main professional courses in medical laboratory technology. Since the epidemic in 2020, universities across the country have been actively responding to the call of the Ministry of Education to "suspend classes without stopping school" and adopting various teaching methods such as online teaching, catechism teaching, virtual simulation teaching, etc. As a new applied subject course with a high degree of knowledge and technology intensity and a unique application goal, Clinical Laboratory Instruments and Technology has undergone After nearly three years of continuous integration and exploration, our teaching and research department is currently using Shandong Zezhong virtual simulation platform to conduct laboratory classes, replacing the online teaching method adopted by most institutions, and improving teaching quality and implementing teaching reform by continuously developing the teaching mode of this course. In accordance with the spirit of document [2001] No. 4 of the Ministry of Education, combined with the teaching requirements of this course and the construction standards of the national high-quality courses, constantly adhere to the development and practice of the teaching methods of the course, the reform and innovation of teaching methods, so that it can adapt to the teaching needs of the current situation is the focus of this paper.